2019
DOI: 10.1152/ajpregu.00029.2019
|View full text |Cite
|
Sign up to set email alerts
|

Acyloxyacyl hydrolase modulates depressive-like behaviors through aryl hydrocarbon receptor

Abstract: Corticotropin-releasing factor (CRF) regulates stress responses, and aberrant CRF signals are associated with depressive disorders. Crf expression is responsive to arachidonic acid (AA), where CRF is released from the hypothalamic paraventricular nucleus (PVN) to initiate the hypothalamic-pituitary-adrenal axis, culminating in glucocorticoid stress hormone release. Despite this biological and clinical significance, Crf regulation is unclear. Here, we report that acyloxyacyl hydrolase, encoded by Aoah, is expre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
40
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 22 publications
(46 citation statements)
references
References 66 publications
2
40
0
Order By: Relevance
“…Since we recently found increased free AA in spinal cords of female AOAH-deficient mice [ 11 ], we examined phospholipid pools of AA female mice. We used an untargeted shotgun lipidomics strategy consisting of the ordered acquisition of mass ion trap detection to investigate differences in phosphatidyl choline and phosphatiyl ethanolamine (PC and PE, respectively) under positive and negative ionization mode of lipids extracted from spinal cord segments S1-S3.…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…Since we recently found increased free AA in spinal cords of female AOAH-deficient mice [ 11 ], we examined phospholipid pools of AA female mice. We used an untargeted shotgun lipidomics strategy consisting of the ordered acquisition of mass ion trap detection to investigate differences in phosphatidyl choline and phosphatiyl ethanolamine (PC and PE, respectively) under positive and negative ionization mode of lipids extracted from spinal cord segments S1-S3.…”
Section: Resultsmentioning
confidence: 99%
“…Although lipidomics showed that sacral spinal cords of female wild type mice contained more AA-containing PE than AOAH-deficient mice, it was unclear whether AOAH could directly modulate the sequestration of AA among CNS phospholipids. Microarray analyses showed that variant 3 of human AOAH (hAOAH3) was highly expressed in the CNS compared to other hAOAH variants [ 5 , 11 , 26 ]. We generated a recombinant lentivirus encoding hAOAH3 and, after confirming that HEK293 cells lack AOAH expression by immunoblotting (not shown), transduced HEK293 cells with AOAH3 or lacZ to obtain the 293 lenti-hAOAH3 and 293 lenti-lacZ cells, respectively.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations